IMF Survey, Volume 37, Issue 09. (IMF Survey; IMF Survey ;, 2008)
Antoinette Sayeh interview, IMF clarifies surveillance process, Georgia loan, Olivier Blanchard interview, Africa's financial sector, EMU slowdown, EU transfers, sovereign wealth fund principles, United Kingdom outlook, Uruguay's financial issues, Saudi Arabia's oil bonanza, news briefs.